To hire or not to hire recruitment, selection and placement of persons with disability among seven companies in Iloilo City - Agnas, Jallen Samantha
Seven (7) companies in the service industries in Iloilo City were selected through purposive sampling for this study. They are operating from less than a year - 5 years to thirty five (35) years. Two instruments were utilized namely: Employers' Attitudes And Concerns About The Employment Of disabled People Questionnaire Adapted From Mourad Mansour (2009) and To Hire Or Not to Hire : Recruitment Selection, Placement Of Persons With Disability In different Industries In Iloilo City Questionnaire Adapted From Department of Employment - ODEP. Results showed that participants do not proactively recruit PWD. Companies are not hiring PWD because of the following top three main reasons: the PWD safety in the building premises, work performance/quality, and productivity.